2015
DOI: 10.1007/s10147-015-0904-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of certain second primary malignancies in patients treated for well-differentiated thyroid cancer

Abstract: The overall incidence of SPMs was not higher in patients than in controls. The incidence of SPMs in thyroid carcinoma patients was higher in patients <40 years old and patients diagnosed since 1996. The incidence of sarcomas and lymphomas was higher in patients than in controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 27 publications
2
28
1
1
Order By: Relevance
“…Hakala et al . 9 even reported that for young patients (<40 years), the risk of secondary malignancies would dramatically increase. More importantly, the use of 131 I for remnant ablation to reduce the risk of recurrence following thyroidectomy in low risk DTC patients remained controversial 10 11 .…”
mentioning
confidence: 99%
“…Hakala et al . 9 even reported that for young patients (<40 years), the risk of secondary malignancies would dramatically increase. More importantly, the use of 131 I for remnant ablation to reduce the risk of recurrence following thyroidectomy in low risk DTC patients remained controversial 10 11 .…”
mentioning
confidence: 99%
“…Given the higher risk of complications, such procedures should be limited to very experienced surgeons [18][19][20][21][22]. However, as there are no proven benefits concerning long-term outcome [21,[23][24][25] and most thyroid procedures in Switzerland are not performed by subspecialised surgeons, prophylactic lymph node dissection cannot be recommended as a standard procedure in patients with small a PTC without macroscopic evidence of lymph node metastases.…”
Section: No Vascular Invasionmentioning
confidence: 99%
“…An increased incidence of second cancer has been reported after radioiodine treatment for thyroid cancer, but data were conflicting and a causal relationship may be difficult to establish [23][24][25]. An increased risk of second malignancies is definitely proved when cumulative exposures exceed 37 GBq (1000 mCi).…”
Section: Nuclear Medicine Perspectivementioning
confidence: 99%
“…The expanding use of RNT has raised concern regarding potential carcinogenic and leukemogenic effects (Hakala et al 2016;Martinez et al 2017). Research on second primary cancer after RNT has been developing especially on 131 I therapy for hyperthyroidism and differentiated thyroid cancer.…”
Section: Second Primary Cancer In Radionuclide Therapymentioning
confidence: 99%